Effects of irrigation system alterations on the trophic position of a threatened top predator in rice‐field ecosystems. (24th July 2019) - Ohba, Shin‐ya; Suzuki, Kodai; Sakai, Yoichiro; Shibata, Jun‐ya; Okuda, Noboru
Abstract: Rice fields serve as alternative habitats for wetland species, and their recent reduction in area due to land conversion is considered one of the main human drivers of wetland biodiversity loss. Even for existing rice fields, physico‐chemical disturbances, such as farmland consolidation and agrochemical application, also have negative effects on wetland biodiversity. For fish that inhabit rice fields for at least part of their life history, differences in water level between rice fields and irrigation ditches caused by irrigation system improvements are critical to their abundance by preventing their access. The ecological impact of differences in water level may extend to the foraging habits and trophic positions of the top predators in rice fields, resulting in the alteration of wetland food webs. Here, we investigated how physical disruptions to habitat networks affect food‐web properties in rice‐field ecosystems. We conducted stable nitrogen and carbon isotope analysis on a threatened giant water bug, Kirkaldyia deyrolli, to estimate its trophic position as an indicator of food‐chain length. Based on field observations, we found that fish that were at a high trophic position were only available to K. deyrolli in rice fields where there were no physical barriers blocking access to the network of habitats, and the diets of K. deyrolli included fish prey (18%, based on visual observation). The stable isotope analysis revealed that the trophic position of K. deyrolli was significantly lower in rice fields with physical barriers (no fish/10 dips by a dip net) than in those without physical barriers (5.6 fish) due to the absence of fish in locations with barriers. In conclusion, our study demonstrates that physical alterations are important to community composition and food‐web properties in rice‐field ecosystems because they can act as barriers to fish.